The Effect of Mind Maps Strategy on Deneloping Critical Thinking in Islamic Education for Eleven Grade Students in Jordan - Mahmoud Alsalti; Mousa Alkhateeb; Mohammed Abu Ali (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The present study aims at identifying the effect of using mind maps on developing critical thinking among eleven grade secondary students in Jordan. The study adopted the semi-experimental approach. The tool (the critical thinking test in Islamic education), prepared by the researcher, was applied. On a random sample of two eleven-grade students in the Theban Secondary School for Boys, affiliated to the Directorate of Education, Madba Governorate during the academic year 2018/2019, for Division (C) as an experimental group, consisting of (30) students, and Division (A) as a control group. It consisted of (30) students. The results of the (T) test showed that there were statistically significant differences between the average scores of students on the critical thinking test due to the variable of teaching method. In light of the results of the study, the researcher recommended training teachers on the strategy of mind maps in the teaching of Islamic education for its effectiveness in teaching, as well as conducting studies dealing with the introduction of other teaching methods.